2020
DOI: 10.35943/mvmj.2020.21.316
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal toxicity of copper oxychloride in lactating female albino rats

Abstract: Objective: To evaluate the postnatal toxicity of copper oxychloride (COC) in lactating female albino rats. Design: Randomized controlled experimental study. Animals: Eighteen pregnant female albino rats weight 150±10 g and 6-7 week old. Procedures: Eighteen pregnant female albino rats were divided into 3 groups treated orally with copper oxychloride 0, 73.5, 147 mg/kg (equivalent 1/20 and 1/10 of LD50) daily from first day of parturition for 21 days. Female rats and its offspring were euthanized at 21 days o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Finally, we reported that copper oxychloride induced prenatal and postnatal toxicity in female albino rats (53,53,55) On conclusions, copper and copper containing compounds may hazardous to animal and human health as it has genotoxic, developmental and hepatic toxicity.…”
Section: Developmental Toxicity Of Copper Oxychloridementioning
confidence: 98%
“…Finally, we reported that copper oxychloride induced prenatal and postnatal toxicity in female albino rats (53,53,55) On conclusions, copper and copper containing compounds may hazardous to animal and human health as it has genotoxic, developmental and hepatic toxicity.…”
Section: Developmental Toxicity Of Copper Oxychloridementioning
confidence: 98%